Analisis Gerak Servis Pendek Backhand Terhadap Ketepatan Sasaran Atlet Bulu Tangkis Remaja Putra PB. Djagung Malang - Hildhan Umanta Prabasmara; Olivia Andiana; Ahmad Abdullah (Gerak: Journal of Physical Education, Sports, and Health, 2022)
The backhand short serve is a type of service that players must master in badminton, but the problem is that mistakes often occur when making a short backhand serve that makes it not right on target. Therefore, it is necessary to conduct research based on motion analysis that aims to determine the accuracy of the target of the Bacakhand short serve in terms of biomechanical principles. This research used descriptive analytic research with a qualitative quantitative approach. In his research, researchers used instruments such as the angle of the knee joint, shoulder joint, and elbow joint in flexion movements. To analyze it is also assisted by kinovea software. The analysis showed that the movement was relatively good and the shuttlecock showed that it was right on target three times, resulting in elbow joint angles in flexion movements ranging from 133˚-139˚, shoulder joints in flexion movements ranging from 42˚-47˚, and knee joints in flexion movements ranging from 162 -174˚. The angle of the elbow joint that spans a small range can make the punching force large.